ANTIMICROBIAL ACTIVITY OF THE SOLVENT FRACTIONS FROM BULBINE NATALENSIS TUBER - Yakubu, M T; Yakubu, Toyin Musa; Ashafa, A O. T; Afolayan, A J (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Bulbine natalensis Baker has been acclaimed to be used as an antimicrobial agent in the folklore medicine of South Africa without scientific evidence to substantiate or refute this claim. In view of this, the in vitro antimicrobial activity of solvent fractions (ethanol, ethyl acetate, n-butanol and water) from Bulbine natalensis Tuber against 4 Gram positive and 12 Gram negative bacteria as well as 3 fungal species were investigated using agar dilution. The ethanolic extract, n-butanol and ethyl acetate fractions inhibited 75, 87.5 and 100% respectively of the bacterial species in this study. The ethanolic, n-butanol and ethyl acetate fractions produced growth inhibition at MIC range of 1-10, 3-10 as well as 1 and 5 mg/ml respectively whereas the water fraction did not inhibit the growth of any of the bacterial species. Again, it was only the ethyl acetate fraction that inhibited the growth of Shigelli flexneri, Staphyloccus aureus and Escherichia coli. The ethanolic, ethyl acetate and n-butanolic fractions dose dependently inhibited the growth of Aspergillus niger and A. flavus whereas the water fraction produced 100% growth inhibition of the Aspergillus species at all the doses investigated. In contrast, no growth inhibition was produced on Candida albicans. The growth inhibition produced by the solvent fractions of B. natalensis Tuber in this study thus justifies the acclaimed use of the plant as an antimicrobial agent. The ethyl acetate fraction was the most potent.